Open star clusters in the Milky Way: comparison of photometric and trigonometric distance scales based on Gaia TGAS data - Kovaleva, Dana A.; Piskunov, Anatoly E.; Kharchenko, Nina V.; Röser, Siegfried; Schilbach, Elena; Reffert, Sabine; Yen, Steffi Xiang-Ting (Arxiv, 2017)
The global survey of star clusters in the Milky Way (MWSC) is a comprehensive list of 3061 objects that provides, among other parameters, distances to clusters based on isochrone fitting. The Tycho-Gaia Astrometric Solution (TGAS) catalogue, which is a part of Gaia data release 1 (Gaia DR1), delivers accurate trigonometric parallax measurements for more than 2 million stars, including those in star clusters. We compare the open cluster photometric distance scale with the measurements given by the trigonometric parallaxes from TGAS to evaluate the consistency between these values. The average parallaxes of probable cluster members available in TGAS provide the trigonometric distance scale of open clusters, while the photometric scale is given by the distances published in the MWSC. Sixty-four clusters are suited for comparison as they have more than 16 probable members with parallax measurements in TGAS. We computed the average parallaxes of the probable members and compared these to the photometric parallaxes derived within the MWSC. We find a good agreement between the trigonometric TGAS-based and the photometric MWSC-based distance scales of open clusters, which for distances less than 2.3 kpc coincide at a level of about 0.1 mas with no dependence on the distance. If at all, there is a slight systematic offset along the Galactic equator between $30^°$ and $160^°$ galactic longitude.
Gesehen am 26.03.2018